1997
DOI: 10.1088/0953-8984/9/31/019
|View full text |Cite
|
Sign up to set email alerts
|

Field dependence of the magnetic quantum phase transition in MnSi

Abstract: The dependence on pressure (P ) and field (H ) of the magnetic phase diagram of MnSi has been investigated by means of measurements of the AC susceptibility (χ ) up to 16 kbar and 7 T at temperatures down to 30 mK. For ambient pressure, we report on a peak in χ above T c at a characteristic temperature T m that rises quickly with field. The pressure dependence of T m is found to be strongly analogous to that of the zero-field transition to long-range order at T c . Features of χ in the field versus temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
113
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(128 citation statements)
references
References 29 publications
14
113
1
Order By: Relevance
“…figure 2) and the calculated χ(H) dependence ( figure 7(c)). Experimentally the characteristic U-shaped anomaly in χ ac (H) indicating the A-phase area has also been observed in MnSi [27,30], Mn 1−y Co y Si and Mn 1−z Fe z Si [8]. These observed anomalies are very similar to the calculated functions χ(H) shown in figure 7(c) which correspond to the hexagonal Skyrmion lattice.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…figure 2) and the calculated χ(H) dependence ( figure 7(c)). Experimentally the characteristic U-shaped anomaly in χ ac (H) indicating the A-phase area has also been observed in MnSi [27,30], Mn 1−y Co y Si and Mn 1−z Fe z Si [8]. These observed anomalies are very similar to the calculated functions χ(H) shown in figure 7(c) which correspond to the hexagonal Skyrmion lattice.…”
Section: Discussionsupporting
confidence: 79%
“…Nevertheless, these studies have accumulated an impressive database on peculiarities of magnetic properties in this enigmatic area. Together with earlier observations [22,24,25,26,27,29,30] and recent theoretical findings [10,47,48] the following important conclusions about the physical nature of the precursor region can be drawn: (i) It consists of a multiplicity of modulated states which have complex multi-dimensional textures, and (ii) precursor states are fundamentally different from regular chiral modulations, as theoretically motivated in [10,48].…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…AC magnetic susceptibility measurements on high purity single crystals demonstrated that the magnetic phase transition at T C changes from second order to first order at P ≈ 12 kbar. Additionally the existence of itinerant metamagnetism corroborates the presence of a local minimum in the free energy [178,179].…”
Section: Mnsisupporting
confidence: 54%
“…[29]. Here ρ and χ indicate that the helical ordering temperature T c was determined by measurements of the electrical resistivity [171] and magnetic susceptibility [178,179], respectively. ENS denotes elastic neutron scattering [180] that identified the cross-over temperature scale T 0 to the partial order.…”
Section: Cein 3 and Cemin (M = Co Ir Rh)mentioning
confidence: 99%